McDonald's global expansion : adaptation and differences in taste - Baack, Daniel W., (SAGE knowledge. Cases., 2016)
There is no doubt that McDonald's has been successful in developing and maintaining a recognizable global brand. This case study examines the McDonald's global brand strategy and evaluates the adaptations that the company makes for local, national markets.